P588 T cell response to SARS-CoV-2 mRNA vaccines by an interferon-gamma release immunoassay in patients with Inflammatory Bowel disease receiving anti-TNF and thiopurine treatment. (21st January 2022) - Mayorga Ayala, L F; Herrera-deGuise, C; Esperalba, J; Martinez-Gomez, X; Céspedes Martinez, E; Robles Alonso, V; Jimenez, A; Perez Martinez, Z; Oller, E; Ibarz, A; Fernandez-Naval, C; Martinez-Gallo, M; et al.
Abstract: Background: Treatment with anti-TNF agents and thiopurines has been associated with an impaired immune response to some vaccines. SARS-CoV-2 vaccination is very effective in healthy individuals, but studies in inflammatory bowel disease (IBD) populations are scarce, especially regarding T cell response. We aimed to evaluate the T cell and antibody response in a cohort of IBD patients on anti-TNF and thiopurine treatment who received two doses of the SARS-CoV2 mRNA vaccine. Methods: An observational, prospective study was carried out at our IBD clinic. We included Crohn's disease (CD) and Ulcerative colitis (UC) patients receiving anti-TNF as monotherapy or anti-TNF + thiopurine (combo) or thiopurines only for at least six months at inclusion. Blood samples were drawn for interferon-gamma release assay (IGRA) and antibody determination six (+/- 2) weeks after the second vaccine dose. The specific T cell response to SARS-CoV-2 was determined by IGRA using Qiagen® QuantiFERON® SARS-CoV-2 RUO tubes with a patented Spike protein combination. Interferon-gamma was measured by CLIA using the LIAISON® QuantiFERON-®TB Gold Plus assay. As there is no validated cut-off point, we used those obtained in a cohort of 20 healthy health professionals published by our group (doi.org/10.1016/j.medcli.2021.09.013). Antibodies to the Spike (S) SARS-CoV-2 protein were analyzed by CLIA. Adverse events (AEs) and clinical activity were recorded. Results: We recruited 148 IBD patients, 57 treated with anti-TNF monotherapy, 53 with combo, and 38 with thiopurine only. Seventy percent had CD, and 60% were male. Using the cut-off value of the cohort mentioned above, the T-cell response was positive in 92% of anti-TNF monotherapy, 83% in combo, and 87% of the thiopurine group (p=ns). The anti-S antibodies were positive in 100% of our cohort. There were no changes in disease activity rates after the second vaccination, nor were severe AEs detected. Conclusion: SARS-CoV-2 mRNA vaccination was very effective in IBD patients receiving anti-TNF (combo or monotherapy) or thiopurine treatment as measured by both T cell and antibody response. IGRA-specific tests may constitute a valuable tool in assessing cellular immunity in immunocompromised patients.